2019
DOI: 10.1039/c9ra00333a
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal mediated phytotoxic impact on winter wheat: oxidative stress and microbial management of toxicity byBacillus subtilisBM2

Abstract: The bacterial management of heavy metal toxicity to durum wheat under a metal stressed environment was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 84 publications
1
16
0
Order By: Relevance
“…The decreased uptake of Cd in microbial inoculated plants under immobilizing agents might be due to the enhanced Cd immobilization in soil [13][14][15]47,73]. These results are substantiated by the findings of other researchers as well [74][75][76]. Enterobacter sp.…”
Section: Discussionsupporting
confidence: 77%
“…The decreased uptake of Cd in microbial inoculated plants under immobilizing agents might be due to the enhanced Cd immobilization in soil [13][14][15]47,73]. These results are substantiated by the findings of other researchers as well [74][75][76]. Enterobacter sp.…”
Section: Discussionsupporting
confidence: 77%
“…Figures 1 and 2 demonstrated that different communities, which also showed differences in the population number, thrived in the activated sludge as evidenced by the appearance of different colonies when cultured in Cu-containing media. The observation thus suggests that different genetic and physiological background may contribute to the growth of different microbial communities, as also suggested by Rizvi et al (2019) that differences in the number of microorganisms population may be attributed to differences in nutrients composition in the growth media, genetic background, and growth conditions.…”
Section: Isolation and Characterization Of Copper Resistant Bacteriamentioning
confidence: 62%
“…Phytostabilization (the conversion of chemicals to less mobile and active forms) can employ plants with high resistance to HM, localizing HM mainly in the root system (Chaney & Mahoney, 2014). Phytoremediation, an emerging technique makes use of plants and their associated microbes to clean up heavy Rizvi et al (2019) Notes.…”
Section: Bioremediationmentioning
confidence: 99%